A meta-analysis of the utility of the neutrophil-to-lymphocyte ratio in predicting survival after pancreatic cancer resection. Issue 5 (May 2018) - Mowbray, Nicholas G.; Griffith, David; Hammoda, Mohammed; Shingler, Guy; Kambal, Amir; Al-Sarireh, Bilal
Abstract: Background: The neutrophil-to-lymphocyte ratio (NLR) is thought to reflect cancer disease burden. To assess the prognostic ability of the NLR on overall survival in patients with resectable, pancreatic cancer a meta-analysis of published literature was undertaken. Method: A systematic review was performed independently by two authors using PubMed, Ovid MEDLINE and Embase databases. Included studies detailed the pre-operative NLR and overall survival of pancreatic cancer patients. Results: Of the 214 studies retrieved using the search strategy, 8 studies involving 1519 patients were included in the meta-analysis. Only one study did not find a statistically significant association between a high NLR and OS. The pooled Hazard Ratio was 1.77 (95% CI [1.45–2.15]; p < 0.01). The NLR cut-off values ranged from 2 to 5. There was low to moderate inter-study heterogeneity (I 2 = 31%; p = 0.17), a low risk of intra-study bias, and potentially 3 unpublished (negative) studies. Conclusions: A high pre-operative NLR indicates a worse prognosis than in patients with a low NLR. There is potential to use the NLR to direct therapies. A specific cut-off value has not been established from this study and so further research is required.